Actual problems of Kazakh society of the XIX century in the work of M.-S. publicist Babadjanova (Herald of Journalism, 2016)
Author of the XIX century Muhammad Salih Babadjanov discloses topical issues of Kazakh society of his time. Such as the problem of the place of residence of the local population, the problem of education of young people (in particular the definition of writing), the problem of determining the place in society, health and health care problem, the problem of the relationship and interaction of the Kazakh people with other people, the problem is a simple legal illiteracy of the population and the problem of breeding andconservation of horses for racing.
Keywords: writer; Mohammed Salih Babadjanov; problems; Kazakh people; XIX century